Mekanisme Distribusi Harta Secara Ekonomis dan Non Ekonomis dalam Sistem Ekonomi Islam - Nunung Nurlaela (At-Tauzi : Jurnal Ekonomi Islam, 2017)
Poverty is one of the big problems of countries, especially poor countries or developing countries. Comprehensive discussion regarding this matter, especially how Islam can be a solution to this economic problem, both in the aspect of inequality and the supply of economic goods, is needed in order to find alternative solutions. This study uses a qualitative approach to obtain an analysis related to economic and non-economic distribution mechanisms in the Islamic economic system. The two distribution mechanisms in the Islamic economy are able to stimulate the development of economic interaction on the one hand, but provide protection for parties who lose in the competition for economic mechanisms. Another advantage is that there is a spiritual value in this Islamic mechanism which will be the main driving force for healthy and stable economic interaction